Integration of Heterogeneous Data into Electronic Patient Records - Savoska, Snezana; Ristevski, Blagoj; Blazheska-Tabakovska, Natasha; Jolevski, Ilija; Bocevska, Andrijana; Trajkovikj, Vladimir (My University, 2021)
The deficiency of data for patients with chronic diseases and other diseases and previous medical treatments shows a significant weakness with many patients. Typically, due to the healthcare system insufficiently, patients with comorbidities might not survive the diseases, especially when the disease is novel. The lack of information on genetic disorders in patients they are not aware of also contributes to increased patient deaths. This leads to the need to integrate medical and health data with various biological and other data, especially in pandemic circumstances and the increasing number of patients with chronic diseases. Patients' health data issues are evident, but they are stored in various hospital and public health systems such as electronic health records (EHRs), healthcare institutions, and laboratories. Furthermore, biological data are often not integrated and cannot be used by patients, physicians, and specialists to treat particular diseases. Although the urgent need for healthcare and medical data integration is apparent, personal data protection laws are rigorous. They do not allow much progress in the field without implementing patient healthcare data security and privacy standards. One solution for this issue is establishing a personal health record (PHR) as an integrative system for the patient. Many ontological frameworks have been proposed to unify the record formats, but none of them is accepted as healthcare standards. The efforts towards approving the HL7 standards and the well-known medical codding systems promise future data integrations. Also, some attempts are made to associate particular diseases with data obtained from external environmental sensors that measure disease-related data. Using these data, called exposure data or exposome, one can clarify the increasing symptoms of particular diseases influenced by external factors. This paper proposes a cloud-based model for integrating healthcare and medical data from different sources as EHR, health information systems, and measurement sensors into PHR as the first stage towards integrating patient health data. The medical data, PHR, numerous biological and exposome data, and data obtained from wearables are considered and stored on the cloud following the required data security and privacy standards.
Keywords: Electronic Health Records, Personal Health Records, Internet of Medical Things, Data Integration